Economic crisis and economic thought : alternative theoretical perspectives on the economic crisis - Gabellini, Tommaso, 1990-; Gasperin, Simone, 1990-; Moneta, Alessio (Routledge studies in the history of economics, 2019)
"The ongoing economic crisis has revealed fundamental problems both in our economic system and the discipline which analyses it. This book presents a series of contrasting but complementary approaches in economic theory in order to offer a critical toolkit for examining the modern capitalist economy. The global economic crisis may have changed the world in which we live, but not the fundamental tenets of the discipline. This book is a critical assessment of the relation between economic theory and economic crises: how intellectual thinking impacts on real economic events and vice versa. It aims at challenging the conventional way in which economics is taught in universities and later adopted by public officials in the policymaking process. The contributions, all written by distinguished academics and researchers, offer a heterodox perspective on economic thinking and analysis. Each chapter is inspired by alternative theoretical approaches which have been mostly side-lined from current academic teaching programmes. A major suggestion of the book is that the recent economic crisis can be better understood by recovering such theoretical analyses and turning them into a useful framework for economic policymaking. Economic Crisis and Economic Thought is intended as a companion to economics students at the Master's and PhD level, in order for them to confront issues related to the labour market, the financial sector, macroeconomics, industrial economics, etc. with an alternative and complementary perspective. It challenges the way in which economic theory is currently taught and offered via alternatives for the future."--Provided by publisher.